Maternal Treatment of Spontaneously Hypertensive Rats With Pentaerythritol Tetranitrate Reduces Blood Pressure in Female Offspring. Issue 1 (January 2015) - Wu, Zhixiong; Siuda, Daniel; Xia, Ning; Reifenberg, Gisela; Daiber, Andreas; Münzel, Thomas; Förstermann, Ulrich; Li, Huige
<x xml:space="preserve">Abstract</x> Pentaerythritol tetranitrate is devoid of nitrate tolerance and shows no reproductive or developmental toxicity in animal studies. Recently, pentaerythritol tetranitrate has been demonstrated to reduce the risk of intrauterine growth restriction and the risk of preterm birth in women with abnormal placental perfusion. This study was conducted to test the perinatal programming effect of pentaerythritol tetranitrate in spontaneously hypertensive rats, a rat model of genetic hypertension. Parental spontaneously hypertensive rats were treated with pentaerythritol tetranitrate (50 mg/kg per day) during pregnancy and lactation periods; the offspring received standard chow without pentaerythritol tetranitrate after weaning. Maternal treatment with pentaerythritol tetranitrate had no effect on blood pressure in male offspring. In the female offspring, however, a persistent reduction in blood pressure was observed at 6 and 8 months. This long-lasting effect was accompanied by an upregulation of endothelial nitric oxide synthase, mitochondrial superoxide dismutase, glutathione peroxidase 1, and heme oxygenase 1 in the aorta of 8-month-old female offspring, which was likely to result from epigenetic changes (enhanced histone 3 lysine 27 acetylation and histone 3 lysine 4 trimethylation) and transcriptional activation (enhanced binding of DNA-directed RNA polymerase II to the transcription start site of the genes). In organ chamber experiments, the endothelium-dependent, nitric oxide–mediated vasodilation to acetylcholine was enhanced in aorta from female offspring of the pentaerythritol tetranitrate–treated parental spontaneously hypertensive rats. In conclusion, maternal pentaerythritol tetranitrate treatment leads to epigenetic modifications, gene expression changes, an improvement of endothelial function and a persistent blood pressure reduction in the female offspring.